Perceptions of family caregivers about the use of hypodermoclysis at home - Braga Martins, Simone (2019)
This study aimed to investigate the perceptions of family members in the care of patients about the use of hypodermoclysis at home. A descriptive qualitative investigation was developed in which semi-structured interviews were conducted with 10 participants in a Brazilian home care service. The data will be organized into the y program and will eventually be analyzed by Bardin containment analysis. As a result, the person in charge of caring for the patients expresses concerns and concerns about taking responsibility for the care of the hypodermoclisis, as well as the partner with the patient. However, over time, I recognize that this method facilitates care and enhances patient comfort. It is concluded that the assistance of health professionals can help family members in patient care adapt to the use of hypodermoclisis at home